The Development of A Bioassay Based on Heterologous Expression of M2 Ion-Channel Protein - Prasetyoputri, Anggia; Yuliaty, Neti; Tuharea, Warda; Febyanti, Alisin Febyanti; Sunarko, Bambang; Atmosukarto, Ines I.C (ANNALES BOGORIENSES, 2010)
Emerging resistant viralÂ  strains combined with theÂ  limited availability of antiviralsÂ  inÂ  a pandemic scenario highlight the need for the development of novel influenza antivirals. A bioassay based on the M2 protein of influenza virusÂ  -Â  a potential target for antivirals - was developed to screen endophytic microbial extracts. M2 can be synthesized using PCR, thus eliminating the need for the handling of infectious specimen. Following cloning of the M2 gene into a pET backbone, the resultant plasmid was transformed into BL21 (DE3) pLyss E. coliÂ  cells.Â  Cultures of these cells were set up at 37ï°C following inoculation with a starter culture, to reach an ODÂ  atÂ  600nmÂ  (OD) ofÂ  0.4-0.6.Â  OnceÂ  atÂ  theÂ  requiredÂ  OD,Â  theÂ  cultureÂ  wasÂ  splitÂ  inÂ  twoÂ  aliquotsÂ  and expressionÂ  ofÂ  theÂ  M2Â  proteinÂ  wasÂ  inducedÂ  inÂ  oneÂ  ofÂ  theÂ  duplicatesÂ  withÂ  theÂ  additionÂ  ofÂ  isopropylÂ  Î²-Dthiogalactopyranoside (IPTG). Bacterial growth was monitored at 60 -minute intervals. Exogenous expression ofÂ  theÂ  M2Â  proteinÂ  hasÂ  beenÂ  reported toÂ  decreaseÂ  hostÂ  cellsÂ  viability,Â  resultingÂ  inÂ  lowerÂ  OD 600 values. Our resultsÂ  suggestÂ  thatÂ  theÂ  M2Â  proteinÂ  wasÂ  expressedÂ  andÂ  thatÂ  overexpressionÂ  ofÂ  thisÂ  proteinÂ  resultedÂ  in consistently lower OD 600Â  values of induced cultures compared with that of uninduced cultures. Based on this principle,Â  extractsÂ  canÂ  beÂ  screenedÂ  forÂ  theirÂ  abilityÂ  toÂ  blockÂ  M2Â  functionÂ  asÂ  identifiedÂ  byÂ  increasedÂ  OD 600 values. Â  Keywords: influenza, M2, bioassay, gene synthesis, antiviral